2009
DOI: 10.1002/ijc.24918
|View full text |Cite
|
Sign up to set email alerts
|

Identification of ATP citrate lyase as a positive regulator of glycolytic function in glioblastomas

Abstract: Glioblastomas, the most malignant type of glioma, are more glycolytic than normal brain tissue. Robust migration of glioblastoma cells has been previously demonstrated under glycolytic conditions and their pseudopodia contain increased glycolytic and decreased mitochondrial enzymes. Glycolysis is suppressed by metabolic acids, including citric acid which is excluded from mitochondria during hypoxia. We postulated that glioma cells maintain glycolysis by regulating metabolic acids, especially in their pseudopod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(79 citation statements)
references
References 65 publications
1
78
0
Order By: Relevance
“…Beckner et al [10] reported that glycolytic enzymes are abundant in pseudopodia formed by U87 astrocytoma cells, and that glycolysis alone can support glioma cell migration. Recently, robust migration of glioblastoma cells has been previously demonstrated under glycolytic conditions and their pseudopodia contain increased glycolytic and decreased mitochondrial enzymes [11].…”
Section: Discussionmentioning
confidence: 99%
“…Beckner et al [10] reported that glycolytic enzymes are abundant in pseudopodia formed by U87 astrocytoma cells, and that glycolysis alone can support glioma cell migration. Recently, robust migration of glioblastoma cells has been previously demonstrated under glycolytic conditions and their pseudopodia contain increased glycolytic and decreased mitochondrial enzymes [11].…”
Section: Discussionmentioning
confidence: 99%
“…Upregulation of ACLy has been found in several types of cancer (3136). The mechanism by which ACLy is involved in the survival machinery of cancer cells might be complex.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its role in fatty acid synthesis, ACLY reinforces the Warburg effect by preventing the accumulation of cytosolic citrate, which is a glycolysis inhibitor. 75,90,91 Glucose provides 60% of the carbon used for fatty acid synthesis. 22 The continued export of citrate from the Krebs cycle may cause a carbon deficit, which can be replenished by the anaplerotic flux derived from the metabolism of glutamine to continue fatty acid synthesis and cellular proliferation (Fig.…”
Section: Tumor Cells Synthesize Fatty Acids and Nucleotides At High Rmentioning
confidence: 99%